2017
DOI: 10.1186/s40359-017-0205-0
|View full text |Cite
|
Sign up to set email alerts
|

Resilience or hope? Incremental and convergent validity of the resilience scale for adults (RSA) and the Herth hope scale (HHS) in the prediction of anxiety and depression

Abstract: BackgroundHope and resilience protect against inner vulnerabilities or harsh life circumstances; they explain individual differences in physical or mental health outcomes under high stress. They have been studied in complementary or competing theoretical frameworks; therefore, the study of measures of hope and resilience should be undertaken prior to explore if they are truly value-added for research. This study investigates the convergent and incremental validity of the Resilience Scale for Adults (RSA) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 88 publications
(99 reference statements)
1
19
0
Order By: Relevance
“…The relationship between stress, depression, and anxiety supports compensatory and protective models of resilience. This is also consistent with the results of previous resilience model studies that the higher score of resilience, better able to resist the negative effect of stress, and the more positive the psychological health [ 6 , 28 , 51 ]. However, in the study of resilience in adolescents, resilience only regulating the relationship between stress and depression not between stress and anxiety [ 32 ].…”
Section: Discussion and Limitationssupporting
confidence: 92%
See 2 more Smart Citations
“…The relationship between stress, depression, and anxiety supports compensatory and protective models of resilience. This is also consistent with the results of previous resilience model studies that the higher score of resilience, better able to resist the negative effect of stress, and the more positive the psychological health [ 6 , 28 , 51 ]. However, in the study of resilience in adolescents, resilience only regulating the relationship between stress and depression not between stress and anxiety [ 32 ].…”
Section: Discussion and Limitationssupporting
confidence: 92%
“…That is to say, the hypothesis that resilience moderated the relationship between stress and depression and anxiety has been confirmed. Previous studies have also found that resilience can partially moderate stress and other psychological and emotional problems [ 6 , 28 ]. To some extent, resilience can relieve depression and anxiety caused or aggravated by stress.…”
Section: Discussion and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…R. Morote et al write in work [9] about RSA and about the Herth Hope Scale (HHS), she was designed as a multi-facet instrument. The HHS evaluates aspects of particularized hope (time-valued outcome) as well as a generalized sense of transcendence and meaning.…”
Section: Resultsmentioning
confidence: 99%
“…Morote et al (Morote, Hjemdal, Krysinska, Martinez Uribe, & Corveleyn, 2017 ) found an important relationship between resilience and hope-mediated subjective emotional well-being using the HHI scale. Pleeging et al (Pleeging et al, 2019 ) highlighted the evaluation of the emotional component of hope when using the HHI scale, that is, the concept of hope as an experience and focus “aimed at gaining control over emotions rather than over external circumstances” (p. 2).…”
Section: Discussionmentioning
confidence: 99%